The Effectiveness of Misoprostol Single Dose Oral for Evacuation of Incomplete Abortion - Eka Rusdianto Gunardi; Affan Solihin (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2019)
This study is aimed to find out the effectiveness of oral 600 mcg single dose misoprostol for the evacuation of conception remnant in cases of incomplete abortion. This research is done by quasi experimental method with one group pretest – posttest design. The population of the study is all women who were diagnosed with incomplete abortion in less than 12 weeks of gestation in Cipto Mangunkusumo National general Hospital and affiliations hospital from June 2018 to June 2019. Women who met the study criteria, was treated with oral misoprostol 600 mcg single dose and then undergo conception evacuation evaluation and side effects evaluation. Effectiveness evaluation was seen after 7 days of single dose 600 mcg of misoprostol by measuring <15 mm endometrial thickness on transvaginal ultrasound. The effectiveness of using single dose oral misoprostol 600 mcg in the study participants was 93.55%, which were 29 out of a total of 31 participants. The side effects experienced after being given misoprostol were bleeding with less than the same amount as menstruation (71.0% and 9.0%), diarrhea (6.5%), and shivering (67.7%), and not found side effects of vomiting. Based on data analysis using paired T test before and 24 hours after administration of misoprostol, there was a significant difference between endometrial thickness (p value <0.001). Misoprostol 600 mcg per oral dose is effective for the evacuation of retained conception tissue of incomplete abortion at less than 12 weeks gestation, so that it can be an alternative non-operative method of evacuating retained conception tissue in incomplete abortion cases other than the operative method. Side effects found were bleeding, diarrhea, and chills. Side effects of vomiting were not found in this study.